2021
DOI: 10.1158/2159-8290.cd-20-0812
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutically Increasing MHC-I Expression Potentiates Immune Checkpoint Blockade

Abstract: Immune checkpoint blockade (ICB) therapy revolutionized cancer treatment, but many patients with impaired MHC-I expression remain refractory. Here, we combined FACS-based genome-wide CRISPR screens with a data-mining approach to identify drugs that can upregulate MHC-I without inducing PD-L1. CRISPR screening identified TRAF3, a suppressor of the NFκB pathway, as a negative regulator of MHC-I but not PD-L1. The Traf3-knockout gene expression signature is associated with better survival in ICB-naïve patients wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(118 citation statements)
references
References 95 publications
(106 reference statements)
3
92
0
Order By: Relevance
“…BO-112 restored MHC-I expression through an NF-κB mediated mechanism and independent of NLRC5. A recent study used a CRISPR screening approach to identify factors that decouple the regulation of MHC-I and PD-L1 ( 99 ). It was found that depletion of TRAF3 upregulated MHC-I through the NF-κB pathway and TRAF3 small molecule inhibitors increased immuno-sensitivity of cancer cells specifically through MHC-I expression.…”
Section: Therapeutic Strategies To Enhance Mhc-i Expressionmentioning
confidence: 99%
“…BO-112 restored MHC-I expression through an NF-κB mediated mechanism and independent of NLRC5. A recent study used a CRISPR screening approach to identify factors that decouple the regulation of MHC-I and PD-L1 ( 99 ). It was found that depletion of TRAF3 upregulated MHC-I through the NF-κB pathway and TRAF3 small molecule inhibitors increased immuno-sensitivity of cancer cells specifically through MHC-I expression.…”
Section: Therapeutic Strategies To Enhance Mhc-i Expressionmentioning
confidence: 99%
“…Collectively, these two mechanisms may partially explain why higher IR-induced neoantigen load in MM samples was not associated with better prognostic outcome. This result also suggests that splicing inhibitors could possibly boost the efficacy of immune checkpoint blockade therapy in MM by activating MHC-I presentation [ 46 , 47 ]. Further analysis with integrated multi-omics data from different aspects of the immune landscape is needed to further understand the potential determinants of responsiveness to cancer immunotherapies in MM.…”
Section: Discussionmentioning
confidence: 99%
“…Critical effectors have been identified through forward genetic approaches [92][93][94]. The discovery of these evasion mechanisms has greatly accelerated with CRISPR screening, which identified pathways involved in the upregulation of checkpoint inhibition [36,95,96], downregulation of MHC processing [70,95,97] altering cytokine signaling [98][99][100][101], and autophagy [102]. In their landmark paper, Manguso and colleagues performed a series of in vivo CRISPR screens in Tcra -/and C57BL6 mice treated with either irradiated tumor vaccine…”
Section: Initiation Of B Cell Responsesmentioning
confidence: 99%